Legal tech and the future of civil justice - Engstrom, David Freeman (Cambridge University Press, 2023)
New digital technologies, from AI-ﬁred 'legal tech' tools to virtual proceedings, are transforming the legal system. But much of the debate surrounding legal tech has zoomed out to a nebulous future of 'robo-judges' and 'robo-lawyers.' This volume is an antidote. Zeroing in on the near- to medium-term, it provides a concrete, empirically minded synthesis of the impact of new digital technologies on litigation and access to justice. How far and fast can legal tech advance given regulatory, organizational, and technological constraints? How will new technologies affect lawyers and litigants, and how should procedural rules adapt? How can technology expand - or curtail - access to justice? And how must judicial administration change to promote healthy technological development and open courthouse doors for all? By engaging these essential questions, this volume helps to map the opportunities and the perils of a rapidly digitizing legal system - and provides grounded advice for a sensible path forward. This book is available as Open Access on Cambridge Core.